Analisis Debit Limpasan Permukaan (Runoff) Berdasarkan Periode Ulang 2, 5, dan 10 Tahun di Desa Dukuh Bareng, Kecamatan Krian, Kabupaten Sidoarjo - Eko Saputra Ramadhani; Faradlillah Saves (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Flooding is one of the hydrometeorological disasters that frequently occurs due to high rainfall intensity, land use changes, and the limited capacity of drainage systems in conveying surface runoff. Dukuh Bareng Village, located in Krian District, Sidoarjo Regency, is an area that often experiences inundation and flooding during periods of increased rainfall. This condition indicates the need for appropriate mitigation efforts through the planning of flood control infrastructure. This study aims to analyze surface runoff discharge based on hydrological data with specific return periods. The research methods include collecting rainfall data from several rain gauge stations around the study area and conducting hydrological analysis to determine the magnitude of runoff discharge. The results show that the surface runoff discharge increases with higher return periods of 2, 5, and 10 years, influenced by the increase in rainfall intensity. The highest discharge occurs in Sub-watershed 3, reaching 0.111 m³/s for the 10-year return period, which is influenced by the larger catchment area. Meanwhile, Sub-watershed 2 has a smaller discharge due to infiltration in open land areas. Overall, the magnitude of runoff discharge is affected by the catchment area, land use, and rainfall intensity.